Iceland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper analyzes the explosion of tourism in Iceland, which has surged above all expectations. The number of tourists has almost quadrupled since the Eyjafjallajokull eruptions in 2010, establishing tourism at the heart of the economy. Tourists do not seem to be driven mainly by rising incomes at home, nor have they been deterred by rising costs on the back of krona appreciation-which leaves Iceland's tourism boom largely unexplained by standard econometric models. Instead, Iceland's natural wonders, welcoming atmosphere, general safety, improving connectedness, and social media outreach have drawn in visitors. Going forward, tourism is likely to grow less rapidly than in recent years, yet remain at strong levels.